(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s ((3eMeO bfGhi eMeO s)
(3ChdgG (B:s
(3NQhL eMeO Hf YHO Gddg Hf MSf hebJdg (B: (3bGdhG (B:(3CbHd eMeO GHf YHO Gddg Hf MSf ai hdGjI QHGM Hf YKeGf Hf MjGf GdeQi GdeOjfI ai eFI hNeSjf , hgh Ydi MeGQ , hjbGd Ydi CJGf s
(3BNQgG (B:s
(3hbGd CHh GdMSf GdeOGFfi (B: (3cGf jWYf ai fSH YHO GdLHGQ hcGf TjYjkG bGdhG (B: (3bOe MQH Hf RjGO Ydi GdefUhQ ai hLhg Cgd NQGSGf acJH Edi hLhg Cgd NQGSGf ai CeQg abJd HHdN Je gPG GdLRA , hjdjg GdLRA GdQGHY , hChdg CeQ YeQh Hf YHjO ai NdGaI Gdefs
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI GdKGfjI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
Keywords: (3GdJGQjNs